The role of custom in controlling discretionary exchange issues in contemporary financial transactions - Alsahhar, AbedAlrahem Ahmed (Journal of Economic, Administrative and Legal Sciences, 2023)
This research will address the role of custom in controlling important and contemporary issues of the provisions of financial transactions, which are the issues of discretionary exchange, the rooting for this role, and setting controls that are considered a criterion, determining the course of the provisions of discretionary exchange in our contemporary transactions, and the consequent jurisprudential impact, This research will contribute to solving the problems of discretionary intercourse in many modern transactions that occur through modern means of communication, or by using new technologies, and this solution is through knowing the controls that control issues of intercourse, which custom contributed to finding, not by addressing all the particles and branches of jurisprudence, Thus, it is an unprecedented fundamentalist study in two respects: the first: it shows the role of custom in classifying the issues of discretionary interaction, and its role in determining values, disposition and guarantee, and second: in shaping the conclusion and the result in the form of an officer or a standard that will make it easier for scholars to know the limits and the space in which custom intervenes in Adjust discretionary handling issues.
Keywords: the importance of custom; discretionary exchange; the role of custom in contemporary transactions; the role of custom in directing rulings; custom and exchange; controls of discretionary exchange